Failure of plastic panels due to drop impact - Wee, Alvin Jie Hong. (2010)
The impact resistance of a material is an important consideration of service life and product safety and liability. This project aims to investigate the effect of impact velocity and impact weight on impact resistance by conducting Dynatup drop impact testing on acrylic and polycarbonate. It is concluded that the higher the velocity, the higher is the maximum load and maximum deflection for both acrylic and polycarbonate. The heavier the impact mass, the maximum load is lower but the maximum deflection is higher for acrylic. The heavier the impact mass, the higher is the maximum load and maximum deflection for polycarbonate. The maximum load is higher for polycarbonate than acrylic whereas the maximum deflection is higher for acrylic than polycarbonate. It is also found out that the higher the tensile velocity, the higher is the maximum load and elongation for both acrylic and polycarbonate. Recommendations on possible ways to further investigate impact resistance of a material are suggested.